Middle-distance runners` skill-specific functionality profiling study - Krivoruchenko, E. V.; Yakovlev, P. I.; Petrov, M. V.; Artamonova, M. G. (Theory and Practice of Physical Culture, 2018)
The study profiles the middle-distance runners` skill-specific functionality by the heart rate variability indices using a factor analysis. The factors of different physiological effects selected for the study purposes were as follows: initial autonomic balance; sympathetic effects; vagal effects; humoral-metabolic effects; total neurohumoral controls; and unstable conditions. The combination and specific gravities of the factors were found skills-specific. The functionality tests of the sample groups showed dominance of the following factors in the following skill classes: initial autonomic balance (49%) in Class II; and total neurohumoral control after physical loads in Class I and CMS (42% and 48%, respectively). Findings of the factor analysis show that the heart rate variability indices shall be taken into account in the prospects` selection process and competitive progress forecasts in the training progress tests and analyses.